Mobile Based Barcode System - Salem Eshtewi, Nada; Salem Eshtewi, Abdalla (Libyan International Medical University, Faculty of Information Technology, 2019)
Abstract:After examining the traditional barcode system, several  problems are found, the following poster attempts to  reduce  these  problems   by   presenting  a   mobilebased  barcode  system.  The  proposed software will also  enhance  the  customer  experience  in  the store by facilitating the buying process.
Linear 1 Dimensional  (1D) Barcodes are  printed  black  strips  of  vertical bars attached  to  almost  every  product  in  stores, used to  encode less  than  20  digits  of  numbers,  scannable by  a  reading  device,   presenting a  link  between   computers  and  the  physical   world. By 1D  it is  meant  that they are  scanned in  one  direction  (horizontally), another type of barcodes scanned in both directions  is known as  the 2  dimensional  barcode (2D) .  Barcodes  play  an  essential   role   in   point   of   sale  systems,  global  supply  chain  management,  advertisement,  identification,  and the safe delivery   of   health  care   services.  This  poster  propose   a   mobile  based  barcode system. [1